Penguatan Pendidikan Karakter Mahasiswa Universitas Terbuka Melalui Habituasi Kegiatan Kemahasiswaan - Kusnadi, Kusnadi; Purwantiningsih, Ary; Sardjiyo, Sardjiyo (Universitas Negeri Malang, 2024)
The purpose of writing this article is to describe the field of student activities at the Open University and analyze the strengthening of student character education through habituation of student activities. The method used in this study is a mixed research design or sequential explorative design. Student activities at the Open University are categorized in six areas, namely the fields of reasoning and science, skills, interests and talents, entrepreneurship, welfare, and social concern. Student involvement in student activities has a great impact on student character. This can be seen from the data that shows that 73.5 percent of students have a participatory character and a high work ethic, 97.1 percent of students have a sense of empathy and solidarity, and 87.9 percent of students have a spirit of leadership and integrity. Student activities in the field of reasoning and science can form the character of active participation, the field of interests and talents can form a work ethic, the field of skills strengthens the character of mutual respect in diversity, the field of entrepreneurship becomes a means of habituating leadership, and the field of welfare and social concern can form students with high integrity